Analysis and Evaluation of Thoroughness and Accuracy of Prescriptions for BPJS Hypertension Outpatients at Hospital X in Bandung City - Caroline, Stefania; Madalena, Louis; Hutapea, Albert Manggading (Jurnal Biologi Tropis, 2024)
The evaluation of prescription thoroughness and accuracy is essential to ensure the quality of pharmaceutical services in health facilities, particularly in pharmaceutical installations. This study aims to assess the patterns of antihypertensive drug use among outpatients with hypertension, evaluate the thoroughness and accuracy of prescriptions, and identify gaps in prescription information. Hypertension, a significant and life-threatening condition that has a high mortality rate, with age being a major risk factor. The study used a descriptive method with a retrospective approach, guided by the JNC VIII 2014 guidelines for hypertension management. Results showed that 35% of patient prescriptions lacked thorough information. he results showed that the most prescribed antihypertensive drugs were Calcium Channel Blockers (CCB) (30%), followed by Beta Blockers (27%), Angiotensin Receptor Blockers (ARB) (26%), Angiotensin-Converting Enzyme (ACE) Inhibitors (10%), and Cardioselective Beta Blockers (5%).